Peningkatan Kemandirian Perekonomian Masyarakat melalui Program Desa Vokasi Berbasis Kecakapan Hidup dan Pendidikan Kewirausahaan Masyarakat - Tb Ai Munandar; Harsiti Harsiti; Yani Sugiyani (Wikrama Parahita : Jurnal Pengabdian Masyarakat, 2018)
A problem frequently occuring in our society is a number of jobless  that has become more and more. Unbalance amount of job vacancies and job seekers has become the cause of the problem. The unideal condition happened because of less empowering local potency which creates independent local economy, especially in villages. In addition, most villagers have less skills than  those who live in cities and towns to take their parts in job seeking competitions. The Program of Community Service for Empowering Society, frequently run by Universitas Serang Raya, may become an alternative to break the problem. The program set in Cening, a village in Cikedal, Pandeglang, has main goal to empower the villagers particulary housewives and those in productive age by producing some traditional snacks which have high selling value. Moreover, they are motivated and trained for doing packaging and marketing their products incompeting with other local products. The result of the program is a team of small community business entrepreneurs of peculiarly local snack products.